Towards a sulfur clean fuel: Deep extraction of thiophene and dibenzothiophene using polyethylene glycol-based deep eutectic solvents. (15th December 2018) - Lima, Filipa; Gouvenaux, Justine; Branco, Luis C.; Silvestre, Armando J.D.; Marrucho, Isabel M.
Abstract: In this work, extractive desulfurization of model fuel containing dibenzothiophene (DBT) and thiophene (Th) as sulfur compounds was carried out using 16 different Deep Eutectic Solvents (DES) based on polyethylene glycol (PEG) and its precursors. The aim of this study is the reduction of the sulfur content of fuels below the environmental regulation (10 ppm), using PEG-based DES as low-cost extraction media under mild conditions and to compare their extractive performance with that of PEG alone, which by itself is a green solvent. For that purpose, 7 different quaternary ammonium and phosphonium salts were combined with four different molecular weight grades of PEG and PEG precursors such as ethylene glycol and triethylene glycol. The best results were obtained for the DES composed of tetrabutylammonium chloride (TBAC) and PEG400, which showed that it is possible to achieve, in single extraction step, 85% and 68% of extraction efficiency, and deep desulfurization in 2 and 3 cycles, for DBT and Th, respectively. In addition, this DES is not soluble in the model fuel and its extraction capacity is independent on the starting sulfur concentration. Finally, after being reused six times, TBAC:PEG400 DES still maintained 53% and 17% of its capacity, for DBT and Th removal, respectively, and after a regeneration step the performance of the DES was fully recovered.